Preparation method of polymer conductive film doped with ionic liquid
By using sulfonated polyolefin polyol as dopant and ionic liquid doping in aqueous polymer dispersion, the problems of insoluble, refractory, poor processability and poor conductivity of polyaniline in practical applications are solved, and the low cost, high dispersion, high stability and excellent conductivity of polymer conductive films are achieved.
Patent Information
- Application Number
- CN202411927289.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-25
AI Technical Summary
In practical applications, polyaniline has problems such as being difficult to dissolve, melt, poor processability, and poor conductivity. The dopant has poor environmental stability and easy dedoping, making the preparation process complex and costly.
The aqueous polymer dispersion is prepared by using sulfonated polyolefin polyol as dopant by in-situ polymerization, and then doped with ionic liquid in the dispersion and heat curing to form a polymer conductive film.
It has achieved low cost, good dispersion, high stability and excellent conductivity of polymer conductive film, and is suitable for use in the field of flexible sensors.
Smart Images

Figure CN119735839A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer conductive films, and in particular to a method for preparing a polymer conductive film doped with ionic liquid. Background Art
[0002] Conductive polymer materials can be attached to various substrates such as fibers, fabrics, gels, etc., and used to develop flexible sensors, rechargeable batteries, electromagnetic interference shielding, electronic equipment, display equipment, electrodes and other equipment. Compared with other materials, they show better flexibility, biocompatibility, and volume controllability, and have broad application prospects. In recent years, conductive polymer materials have been widely used to achieve the conversion of mechanical energy to electrical energy. Conductive polymer materials are divided into two categories: intrinsic conductive polymer materials and composite conductive polymer materials; among them, intrinsic conductive polymer materials refer to polymers that can conduct electricity themselves, generally conjugated polymers, such as polythiophene, polypyrrole, etc.; composite conductive polymer materials refer to composite materials with conductive ability formed by adding conductive substances to polymer materials through dispersed composites, layered composites, gradient composites, surface composites and other methods.
[0003] Among many conductive polymer materials, polyaniline is widely used in the research of conductive polymer materials due to its advantages such as cheap and readily available raw materials, simple synthesis process, adjustable conductivity, good environmental stability, low permeation threshold, and melt processability. However, due to the rigid structure of the main chain of polyaniline itself and its non-conductivity, as well as the poor solubility caused by the large number of hydrogen bonds inside it, the actual use of polyaniline has been greatly limited.
[0004] Although polyaniline is a soluble polymer, dynamic light scattering experiments reveal that polyaniline has a strong tendency to aggregate in organic solvents. 4 ~10 6 g / mL), the polyaniline molecular chains tend to aggregate at normal concentrations, and a polyaniline dispersion with uniform dispersion and stable particle size cannot be obtained; and the organic solvent added therein is easy to volatilize into flammable gas, which has the risk of causing deflagration, explosion and fire. Moreover, the organic solvent has different degrees of irritation to human skin, mucous membranes, etc., and some of them are carcinogenic and teratogenic, so further improvement is still needed.
[0005] In order to solve the problems of polyaniline such as poor solubility, poor melting point, poor processability and poor conductivity, doping modification is one of the research and development directions. Doping is one of the important modification methods for conductive polymer materials. Through doping, the conductive polymer chain can have electrons or holes with higher energy to form carriers, and the carriers can move in a directional manner in an external electric field. The acid doping modification of polyaniline includes two types: inorganic acid doping and organic acid doping. Among them, although the doping of inorganic acid can improve the working performance of polyaniline, the doped product obtained by this method has the disadvantages of poor environmental stability and easy dedoping. Although the method of organic acid doping can achieve higher product stability, the morphology of the prepared polyaniline is not uniform, the particle size is too large, the preparation process is relatively complicated, and the cost is usually high.
[0006] Therefore, there is an urgent need to develop a dopant and steric stabilizer for polyaniline that is in line with the concept of green development, has low cost, and has a simple synthesis process, and to use this dopant to prepare a polyaniline conductive film with higher dispersibility, stability, conductivity, and is non-volatile and non-flammable. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a polymer conductive film doped with an ionic liquid to solve the above-mentioned problems in the background technology. The present invention uses sulfonated polyolefin polyol as a dopant, prepares an aqueous polymer dispersion by in-situ polymerization, and then dopes the dispersion with an ionic liquid and thermally cures the dispersion to prepare a polymer conductive film. The polymer conductive film doped with an ionic liquid prepared by the present invention has the advantages of low cost, good dispersibility, high stability, and excellent conductive performance.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] One of the technical solutions of the present invention is to provide a method for preparing a polymer conductive film doped with an ionic liquid, comprising the following steps:
[0010] (1) dissolving a polyolefin polyol in a solvent, then adding sulfuric acid to carry out a sulfonation reaction to obtain a sulfonated polyolefin polyol;
[0011] (2) mixing the sulfonated polyolefin polyol, aniline and an oxidant in a solvent and reacting them to obtain an aqueous conductive polymer dispersion;
[0012] (3) adding ionic liquid to the aqueous conductive polymer dispersion, heating and curing, and obtaining the ionic liquid-doped polymer conductive film.
[0013] Preferably, the polyolefin polyol is polyvinyl alcohol.
[0014] Preferably, in step (1), the mass ratio of the polyolefin polyol to sulfuric acid is 2-4:6.67-13.33; the temperature of the sulfonation reaction is 35-55° C., and the time is 0-1 h and is not 0.
[0015] Preferably, the oxidant is ammonium persulfate.
[0016] Preferably, in step (2): the molar ratio of the sulfonated polyolefin polyol to aniline is 2-4:0.67-1.33; the reaction is first carried out at 0-5°C for 4-6 hours, and then at 10-30°C for 10-14 hours.
[0017] Preferably, the ionic liquid is 1-ethyl-3-methylimidazolium hydrogen sulfate; the added amount of the ionic liquid is 1 to 5 wt % of the mass of the aqueous conductive polymer dispersion.
[0018] Preferably, in step (3), the temperature of the heating curing is 40 to 60° C., and the time is 3 to 5 hours.
[0019] Preferably, the solvent is water.
[0020] The second technical solution of the present invention is to provide a polymer conductive film doped with ionic liquid obtained according to the above preparation method.
[0021] The beneficial technical effects of the present invention are as follows:
[0022] The present invention uses sulfonated polyolefin polyol as a dopant, prepares an aqueous polymer dispersion by in-situ polymerization, and then dopes the dispersion with ionic liquid and heat cures it to prepare a polymer conductive film. The polymer conductive film doped with ionic liquid prepared by the present invention has the advantages of low cost, good dispersibility, high stability and excellent conductive performance.
[0023] The sulfonated polyolefin polyol prepared by the present invention can be used as a dopant and a steric stabilizer of polyaniline and is water-soluble, and the synthesis process is simple and the cost is low. By co-doping the sulfonated polyolefin polyol and the ionic liquid into the conductive film, the prepared polymer conductive film can have high dispersibility, stability and conductivity, and is suitable for use in the field of flexible sensors. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1This is a diagram of the color change of the solution during the in-situ polymerization process prepared in Example 1.
[0026] Figure 2 This is a graph showing the particle size distribution test results of the ionic liquid-doped polymer conductive films prepared in Examples 1 to 5 and Comparative Examples 1 to 3.
[0027] Figure 3 The graph is a test result of the conductivity of the polymer conductive membranes doped with ionic liquids prepared in Examples 1 to 5 and Comparative Examples 1 to 3.
[0028] Figure 4 This is a graph showing the elongation at break test results of the ionic liquid-doped polymer conductive films prepared in Examples 1 to 5 and Comparative Examples 1 to 3.
[0029] Figure 5 This is a graph showing the test results of the sensitivity coefficient of the polymer conductive films doped with ionic liquids prepared in Examples 1 to 5 and Comparative Examples 2 to 3.
[0030] Figure 6 Schematic diagram of the microstructure of the ionic liquid-doped polymer conductive membrane prepared in Examples 1 to 5. DETAILED DESCRIPTION
[0031] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0032] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0033] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0034] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.
[0035] Since the discovery of the conductivity of doped polyacetylene in the field, conductive polymers have gradually come into people's view. Doping is one of the important modification methods of conductive polymer materials. This is mainly because conductive polymer materials all have a conjugated structure with alternating single and double bonds, but the intrinsic undoped conductive polymer is almost non-conductive. Its electrons will be trapped in the valence band or conjugated π orbital and cannot move in an external electric field. By using the method of doping polyaniline with organic protonic acid, the doped polyaniline can be dissolved or dispersed in ordinary solvents, alleviating the problem of difficult processing of doped polyaniline.
[0036] There are two doping mechanisms for polyaniline, namely the charge transfer complex mechanism and the proton acid mechanism. The charge transfer complex mechanism believes that polyaniline, like most conductive polymers, will gain or lose electrons in the process of doping, and the dopant will be oxidized or reduced accordingly, eventually forming a product of the dopant ion and the conductive polymer chain. After doping, the conductivity will be greatly improved. The proton acid doping mechanism is a unique doping mechanism for polyaniline. It believes that in the process of doping, there is no gain or loss of electrons on the chain, and the H of the dopant + First, it will enter the imine group, and the positive charge it carries will migrate along the polyaniline main chain and be distributed periodically, which will make the molecular chain positively charged. In order to maintain the overall electrical neutrality, the anions of the dopant will also be adsorbed around the polymer chain. Therefore, it can also be regarded as a salt-forming process.
[0037] The present invention provides a method for preparing a polymer conductive film doped with an ionic liquid, comprising the following steps:
[0038] (1) Dissolve 2-4 mmol of polyolefin polyol in a solvent at 70-90° C., then cool to 35-55° C., slowly add 33-66 wt % concentrated sulfuric acid solution, react for 0-1 h, then wash several times, filter, and dry to obtain sulfonated polyolefin polyol; the synthesis route is shown in Formula 1:
[0039]
[0040] (2) Dissolving 2-4 mmol of the sulfonated polyolefin polyol in a solvent at 75-95° C., adding 0.67-1.33 mmol of aniline at 10-30° C., and dropping 0.22-0.44 mmol of an oxidant at 0-5° C., reacting for 4-6 hours, and then reacting at 10-30° C. for 10-14 hours to obtain a dark green aqueous conductive polymer dispersion; the synthesis route is shown in Formula 2:
[0041]
[0042] (3) adding an ionic liquid to the aqueous conductive polymer dispersion (the amount of the ionic liquid added is 1 to 5 wt% of the mass of the aqueous conductive polymer dispersion), stirring at room temperature to fully dissolve and disperse it, then adding it to a mold, and then thermally curing it in an oven at 40 to 60° C. for 3 to 5 hours to obtain the polymer conductive film doped with the ionic liquid.
[0043] Preferably, the solvent is water.
[0044] The water-soluble conductive film prepared by the water-based processing method of the present invention uses water as a solvent, has the advantages of being environmentally friendly and non-toxic, and does not have the problem of VOC emission, which is in line with the concept of green development.
[0045] Preferably, the polyolefin polyol is polyvinyl alcohol 1788, with a molecular weight of 82,000 and a degree of alcoholysis of 85.0-90.0%.
[0046] After polyaniline is doped with sulfonated polyvinyl alcohol (SPVA), hydrogen bonds and interactions between macromolecular chains are generated, so that the polyaniline is evenly dispersed without aggregation, and plays the role of a steric stabilizer. In addition, partially sulfonated SPVA can be used as a dopant for polyaniline to further reduce the particle size of polyaniline. The doping scheme of the present invention can obtain a conductive polyaniline dispersion with stable dispersion, excellent conductive properties and good water solubility.
[0047] Preferably, the oxidant is ammonium persulfate.
[0048] Ammonium persulfate is used to provide oxidizing properties and promote the in-situ polymerization of aniline monomers to form aqueous polyaniline dispersions. Ammonium persulfate can decompose under mild conditions to produce sulfate ion radicals, which have extremely high oxidation potentials. Compared with other strong oxidants (such as potassium permanganate or hydrogen peroxide), ammonium persulfate can work under milder pH and temperature conditions, avoiding the adverse effects that may be caused by high temperature and high pressure operations.
[0049] Preferably, the ionic liquid is 1-ethyl-3-methylimidazolium hydrogen sulfate.
[0050] As an ionic conductive medium, ionic liquid has the advantages of being simple to use and easy to operate. By doping the conductive polymer of the present invention with ionic liquid, the conductive polymer chain can be provided with electrons with higher energy and space can be provided to form carriers, thereby obtaining an ionic liquid conductive polymer with high conductivity, wide electrochemical window, non-volatile and non-flammable properties.
[0051] The "room temperature" in the present invention is 10-30°C unless otherwise specified.
[0052] The polyvinyl alcohol used in the following examples and comparative examples of the present invention is polyvinyl alcohol 1788, with a molecular weight of 82,000 and a degree of alcoholysis of 85.0-90.0%.
[0053] All raw materials used in the following examples and comparative examples of the present invention are commercially available products.
[0054] Example 1
[0055] A method for preparing a polymer conductive film doped with an ionic liquid, comprising the following steps:
[0056] (1) Polyvinyl alcohol (6.000 g, 0.003 mol) was stirred and dissolved in deionized water (40.000 g, 2.220 mol) at 90°C. After the solution became clear and transparent, the temperature was lowered to 55°C. Then, 40 mL of a 50 wt% concentrated sulfuric acid solution was slowly added dropwise. After the solution was reacted for 0.5 h, the temperature was lowered to room temperature. The reaction solution was then precipitated and washed with anhydrous ethanol. The washing solution was filtered at a pH of about 5 and dried in a vacuum drying oven until constant weight was obtained to obtain sulfonated polyvinyl alcohol (SPVA), which was then sealed and stored.
[0057] (2) Sulfonated polyvinyl alcohol (0.500 g, 2.220 mmol) was dissolved in deionized water (9.500 g). After the solution became clear and transparent, aniline (0.069 g, 0.740 mmol) was added at room temperature. At 4°C, oxidant ammonium persulfate (0.056 g, 0.247 mmol) dissolved in deionized water (1.000 g) was slowly dripped into the reaction solution. After reacting for 5 h, the mixture was reacted at room temperature for 12 h to obtain a dark green aqueous conductive polymer dispersion, which was sealed in a glass bottle and stored at room temperature.
[0058] (3) Take 10.00g of the aqueous conductive polymer dispersion and put it in a sample bottle, add 1-ethyl-3-methylimidazole hydrogen sulfate (the addition amount is 1wt% of the mass of the aqueous conductive polymer dispersion), and stir at room temperature for 2 to 3 hours to allow the ionic liquid to be fully dissolved and dispersed in the aqueous conductive polymer dispersion, then add it to the mold, and then heat cure it in an oven at 60°C for 4h to obtain a polymer conductive film doped with ionic liquid.
[0059] Example 2
[0060] The only difference from Example 1 is that the added amount of 1-ethyl-3-methylimidazole hydrogen sulfate is modified to 2 wt % of the mass of the aqueous conductive polymer dispersion.
[0061] Example 3
[0062] The only difference from Example 1 is that the added amount of 1-ethyl-3-methylimidazole hydrogen sulfate is modified to 3 wt % of the mass of the aqueous conductive polymer dispersion.
[0063] Example 4
[0064] The only difference from Example 1 is that the added amount of 1-ethyl-3-methylimidazole hydrogen sulfate is modified to 4 wt % of the mass of the aqueous conductive polymer dispersion.
[0065] Example 5
[0066] The only difference from Example 1 is that the added amount of 1-ethyl-3-methylimidazole hydrogen sulfate is modified to 5 wt % of the mass of the aqueous conductive polymer dispersion.
[0067] Figure 1 This is a diagram showing the color change of the solution during the in-situ polymerization of polyaniline during the preparation of Examples 1 to 5.
[0068] Figure 6 Schematic diagram of the microstructure of the ionic liquid-doped polymer conductive membrane prepared in Examples 1 to 5.
[0069] Comparative Example 1
[0070] The only difference from Example 1 is that 1-ethyl-3-methylimidazole hydrogen sulfate is replaced by an equal mass of deionized water.
[0071] Comparative Example 2
[0072] The only difference from Example 3 is that 1-ethyl-3-methylimidazolium hydrogen sulfate is changed to 1-ethyl-3-methylimidazolium tetrafluoroborate.
[0073] Comparative Example 3
[0074] The only difference from Example 3 is that 1-ethyl-3-methylimidazolium hydrogen sulfate is changed to 1-butyl-3-methylimidazolium tetrafluoroborate.
[0075] Comparative Example 4 (replaced with a macromolecular acid dopant commonly used in the art)
[0076] The only difference from Example 1 is that only step (2) is performed, and the SPVA in step (2) is replaced by an equal mass of dodecylbenzenesulfonic acid, poly(2-acrylamide-2-methylpropanesulfonic acid), aminosulfonic acid, p-toluenesulfonic acid, and camphorsulfonic acid.
[0077] Effect verification
[0078] (1) Working performance tests were performed on Examples 1 to 5 and Comparative Examples 1 to 3.
[0079] Test conditions:
[0080] The conductivity of the polymer conductive films obtained in Examples 1 to 5 and Comparative Examples 1 to 3 was tested by a four-probe tester. The specific test method is: first, the thickness of the conductive film is accurately measured using a film thickness meter. After turning on the instrument, the specification is first adjusted to "square resistance", and the thickness of the film is input. Then the film is placed directly under the probe and the probe height is adjusted by rotation. The probe is inserted into the sample and the data is stabilized. After multiple readings are taken, the average value is calculated. At the same time, different positions of the sample are measured to reduce errors. The results are shown in Tables 1 and Figure 3 shown.
[0081] The polymer conductive films of Examples 1 to 5 and Comparative Examples 1 to 3 were tested according to GB / T1040-2006 "Determination of tensile properties of plastics". The specific test method is: select several samples of the same type with the same length and width, randomly select one of them, cut a notch with a width of 1 mm in the middle of the sample, and then perform tensile tests on the notched and intact samples respectively, so as to reflect the relationship between stress and strain. The test results are shown in Tables 1 and Figure 4 As shown. The fracture energy is calculated according to formula 1:
[0082]
[0083] In formula 1: w, the toughness of the notched sample at the maximum tensile strength corresponding to the same elongation of the intact sample (MJ / m 3 ), c, notch width (mm), λc, elongation at break of notched sample.
[0084] The strain sensing properties of the polymer conductive films of Examples 1 to 5 and Comparative Examples 2 to 3 were tested using an electrochemical workstation. The specific operation was as follows: First, conductive copper tape was used to wrap around both ends of the sample and clamped with clips at both ends of the wire on the workstation. A curve of current variation over time was obtained by stretching the sample at a fixed voltage. The rate of change of sample resistance was obtained according to Ohm's law. The test results are shown in Tables 1 and Figure 5 As shown. The GF value is a parameter used to measure the sensitivity of the sensor. GF is usually expressed as the ratio of the output electrical signal to the applied external force. Among them, the sensitivity coefficient GF is calculated according to formula 2:
[0085]
[0086] In formula 2: R 0 , the resistance when no strain occurs (Ω); ΔR, the change in resistance with strain (Ω); ε, the strain caused by external force, that is, the length change ΔL and the initial length L 0 ratio.
[0087] The particle size distribution of the polymer conductive films of Examples 1 to 5 and Comparative Examples 1 to 3 was tested. The specific operation was as follows: the particle size of the prepared liquid sample was tested and analyzed using a 90plus PALS laser particle size analyzer produced by Bruker, Germany. First, a small amount of the sample to be tested was weighed with a dropper and dropped into a vessel specifically used for testing. Then, the sample was diluted by adding deionized water several times until it became clear and transparent. The test was repeated three times to avoid accidental experimental errors, so that the particle size distribution curve and the average particle size of the sample to be tested can be obtained. The test results are shown in FIG. Figure 2 shown.
[0088] Test results:
[0089] Table 1 Conductivity, mechanical properties test and sensitivity coefficient of polymer electrolyte
[0090]
[0091] In the field of flexible sensors, the elastic modulus of the material needs to be close to the modulus of human skin (0-1MPa), and the lower the modulus, the better while keeping other properties unchanged; from the data recorded in Table 1, it can be seen that the elastic modulus of Example 1 and Example 2 is relatively too high, and although the elastic modulus of Example 4 and Example 5 is appropriate, the sensitivity is too low; in general, the sensitivity coefficient of Example 3 is the best and the mechanical properties also meet the requirements.
[0092] It can be seen from Table 1 that compared with Comparative Examples 1 to 3, the products of Examples 1 to 5 have excellent working performance. It can be seen that the ionic liquid with the greatest impact on the conductive film is the conductive film prepared by Example 3 with a content of 3wt% of 1-ethyl-3-methylimidazole hydrogen sulfate, and its conductivity is as high as 1.1692mS / mm, the elongation at break is 437.65%, and the sensitivity coefficient is 2.55. The conductivity of the conductive film prepared by changing only the content of the ionic liquid while keeping other conditions unchanged shows a trend of first increasing and then decreasing with the increase of the ionic liquid content. When the ionic liquid content is 4wt%, the conductivity reaches 1.53mS / mm, and then decreases again, but it can be seen that the conductivity of the polyaniline conductive film is significantly improved after adding this ionic liquid. This is mainly because this type of ionic liquid can provide a large number of carriers and have a co-doping effect on polyaniline, so it can significantly improve the conductivity of the conductive film. However, when it reaches a certain content, it will cause the polyaniline doping in the system to be oversaturated, which will cause part of the polyaniline to be dedoped, thereby reducing the conductivity.
[0093] As can be seen from Table 1, the elongation at break of Examples 1 to 5 shows a trend of first increasing, then decreasing, and then increasing as the content of 1-ethyl-3-methylimidazole hydrogen sulfate increases. This is mainly because the rigid imidazole rings on the ionic liquid will form intermolecular interactions with the polymer chains in the system. At the beginning, as the content of the ionic liquid continues to increase, the number of rigid imidazole rings will increase, resulting in an increase in both the elongation at break and the tensile strength; as the content continues to increase, the ionic liquid monomer will act as a diluent in the system, causing the elongation at break of the conductive film to decrease. Therefore, the appropriate addition of ionic liquid is conducive to enhancing the electrostatic interaction in the network, thereby enhancing the internal force of the system, while excessive ionic liquid will destroy the uniformity of the network.
[0094] It can be seen from Table 1 that the overall trend of the sensitivity coefficients of Examples 1 to 5 is to increase first, then decrease, and then increase again. This is mainly because the increase in the content of the ionic liquid in the early stage will increase the number of conductive channels inside the conductive membrane, so the rate of change of resistance caused by deformation will also increase, that is, the sensitivity coefficient will also increase; when the content of the ionic liquid continues to increase, a certain deformation (referring to the deformation caused by the increase in the conductive channels inside the conductive membrane caused by the increase in the content of the ionic liquid) will not cause a large change in resistivity. In summary, this is consistent with the previous laws of conductivity and mechanical properties. Since the spline prepared in Comparative Example 1 can only be stretched and cannot rebound, its sensitivity coefficient cannot be calculated.
[0095] Figure 2 This is a graph showing the particle size distribution test results of the ionic liquid-doped polymer conductive films prepared in Examples 1 to 5 and Comparative Examples 1 to 3.
[0096] Figure 3 The conductivity test results of the polymer conductive membranes doped with ionic liquids prepared in Examples 1 to 5 and Comparative Examples 1 to 3 are shown.
[0097] Figure 4 This is a graph showing the elongation at break test results of the ionic liquid-doped polymer conductive films prepared in Examples 1 to 5 and Comparative Examples 1 to 3.
[0098] Figure 5 This is a graph showing the test results of the sensitivity coefficient of the polymer conductive films doped with ionic liquids prepared in Examples 1 to 5 and Comparative Examples 2 to 3.
[0099] (2) The performance of the aqueous polyaniline dispersion prepared in Example 1 was compared with that of Comparative Example 4, the average particle size of polyaniline was measured, and the cost of the dopant was compared. The test results are shown in Table 2.
[0100] Table 2 Particle size and cost analysis of polyaniline doped with different dopants
[0101]
[0102] As shown in Table 2, compared with other commonly used macromolecular acid dopants in the art, the product obtained by using SPVA as a dopant for polyaniline has the smallest particle size and the lowest cost.
[0103] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a polymer conductive film doped with an ionic liquid, characterized in that: The following steps are involved: (1) dissolving a polyolefin polyol in a solvent, then adding sulfuric acid to carry out a sulfonation reaction to obtain a sulfonated polyolefin polyol; (2) mixing the sulfonated polyolefin polyol, aniline and an oxidant in a solvent and reacting them to obtain an aqueous conductive polymer dispersion; (3) adding ionic liquid to the aqueous conductive polymer dispersion, heating and curing, and obtaining the ionic liquid-doped polymer conductive film.
2. The preparation method according to claim 1, characterized in that: The polyolefin polyol is polyvinyl alcohol.
3. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the polyolefin polyol to sulfuric acid is 2-4:6.67-13.33; the temperature of the sulfonation reaction is 35-55° C., and the time is 0-1 h and is not 0.
4. The preparation method according to claim 1, characterized in that: The oxidant is ammonium persulfate.
5. The preparation method according to claim 1, characterized in that: In step (2), the molar ratio of the sulfonated polyolefin polyol to aniline is 2-4:0.67-1.33; the reaction is first carried out at 0-5°C for 4-6 hours, and then at 10-30°C for 10-14 hours.
6. The preparation method according to claim 1, characterized in that: The ionic liquid is 1-ethyl-3-methylimidazolium hydrogen sulfate; the addition amount of the ionic liquid is 1-5wt% of the mass of the aqueous conductive polymer dispersion.
7. The preparation method according to claim 1, characterized in that: In step (3): the temperature of the heating curing is 40 to 60° C. and the time is 3 to 5 hours.
8. The preparation method according to claim 1, characterized in that: The solvent is water.
9. A polymer conductive film doped with an ionic liquid obtained according to the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of multicolor conducting polymer latex with fluorescent function
CN102675603A
Preparation method of polyion liquid doped soluble conductive polyaniline
CN109762332A
Electronically-conductive polymers
CN1276086A
Conductive polymer-sulfonated polymeric elastomer composite conductive rubber and its preparation method
CN1410486A
Functionalised dopants and conducting polyaniline materials, blends and process therefor
WO2007077569A1